Management Strategies for Skull Base Inverted Papilloma. (July 2016) - Grayson, Jessica W.; Khichi, Sunny S.; Cho, Do-Yeon; Riley, Kristen O.; Woodworth, Bradford A.
Objective: Inverted papilloma attached to the ventral skull base presents a surgical dilemma because surgical removal of the bony pedicle is critical to decrease risk of recurrence. The objective of this study is to evaluate the effectiveness of endoscopic management of skull base inverted papilloma. Study Design: Case series with planned data collection. Setting: Tertiary medical center. Subjects: Patients with skull base inverted papilloma. Methods: Over 7 years, 49 patients with skull base inverted papilloma were referred for surgical resection. Demographics, operative technique, pathology, complications, recurrence, and postoperative follow-up were evaluated. Results: Average age at presentation was 57 years. Twenty-six patients (53%) had prior attempts at resection elsewhere, and 5 had squamous cell carcinoma (SCCA) arising in an inverted papilloma. Six patients (12%) suffered major complications, including skull base osteomyelitis in 2 previously irradiated patients, cerebrospinal fluid leak with pneumocephalus (n = 1), meningitis (n = 1), invasive fungal sinusitis (n = 1), and cerebrovascular accident (n = 1). The mean disease-free interval was 29 months (range, 10-78 months). One patient with SCCA recurred in the nasopharynx (overall 2% recurrence rate). He is disease-free 3 years following endoscopic nasopharyngectomy. Three patients with SCCA had endoscopic resection of the skull base, while 1 subject with inverted papilloma pedicled on the superior orbital roof had an osteoplastic flap in conjunction with a Draf III procedure. All others received endoscopic resection. Conclusions: Removal of the bony pedicle resulted in excellent local control of skull base inverted papillomas. Our experience demonstrates that disease eradication with limited morbidity is attainable with this approach.